Nishkam Karma: The Path for Corporate Social Responsibility - Kumar, Raj (Prabandhan: Indian Journal of Management, 2012)
CSR is a self-regulating mechanism, and is concerned with the inner voice of corporate masters. It is assumed that the teachings of The Gita, specifically the philosophy of Nishkam Karma, offer good direction in the discharge of responsibility towards "tetra bottom line" i.e. people, planet, profit and spirituality. There is no denying the fact that all the great scriptures of all the religions offer immense wisdom for inculcating values and ethical norms in the corporate world, which can be the basic ethical conduct of business. Literature dealing with the interplay between spirituality and business has been growing over the last many years. The prevailing studies on the subject delineate that researchers are doing a commendable research on the role of spirituality in the ethical governance of business. However, the present study is aimed at formulating and systematizing the intuitive wisdom of The Gita in the field of CSR. In this paper, an attempt has been made to study the concept of CSR from the Vedic perspective; to study CSR from the modern perspective; to evaluate the dilemma of CSR in the contemporary globalized regime; and to study the of philosophy of Nishkam Karma and its relevance to CSR practices and initiatives. The philosophy of Nishkam Karma demands freedom from i-me-my-mine syndrome and going beyond realities to sensitivity towards certain interdependent, shared spaces and values. This makes corporate mentors to realize that "beyond profits are more profits". The research is mainly exploratory in nature and is based on qualitative research methodology, which is the interpretation of the teachings of The Gita and other ancient and spiritual literature.